Crystal structure of bis[μ2-(N-(2-hydroxyethyl)-N-methylcarbamodithioato-κS:κS,κS′)]-bis(triethylphosphine-P)-di-silver(I), C20H46Ag2N2O2P2S4 - Yeo, Chien Ing *; Lo, Kong Mun *; Tiekink, Edward R. T. * (De Gruyter Open, 2020)
C20H46Ag2N2O2P2S4, triclinic, P1̄ (no. 2), a = 9.3895(1) Å, b = 13.1597(2) Å, c = 13.1803(2) Å, α = 88.119(1)°, β = 86.601(1)°, γ = 70.173(1)°, V = 1529.22(4) Å3, Z = 2, R gt(F) = 0.0162, wR ref(F 2) = 0.0406, T = 100(2) K.